Options on foreign exchange - DeRosa, David F. (Hoboken, N.J. : Wiley, 2011)
"A comprehensive guide to the world's largest financial market. Foreign exchange is the world's largest financial market and continues to grow at a rapid pace. As economies intertwine and currencies fluctuate there is hardly a corporate entity that doesn't need to use options on foreign exchange to hedge risk or increase returns. Moreover, currency options, both vanilla and exotic, are part of standard toolkit of professional portfolio managers and hedge funds. Written by a practitioner with real-world experience in this field, the Third Edition of Options on Foreign Exchange opens with a substantive discussion of the spot and forward foreign exchange market and the mechanics of trading currency options. The Black-Scholes-Merton option-pricing model as applied to currency options is also covered, along with an examination of currency futures options. Throughout the book, author David DeRosa addresses the essential elements of this discipline and prepares you for the various challenges you could face... Updates new developments in the foreign exchange markets, particularly regarding the volatility surface. Includes expanded coverage of the currency crises and capital controls, electronic trading, forward contracts, exotic options, and more. Employs real-world terminology so you can a firm understanding of this dynamic marketplace.. The only way to truly succeed in today's foreign exchange market is by becoming more familiar with currency options. The Third Edition of Options on Foreign Exchange will help you achieve this goal and put you in better position to make more profitable decisions in this arena"--
Includes bibliographical references and index.
Keywords: Options (Finance); Foreign exchange futures